Reformasi Pelayanan Publik Melalui Government Mobile (Studi di Kabupaten Gorontalo) - Muhammad Nasir Tongkonoo (Jurnal Administrasi Publik, 2015)
Abstract: Government Mobile Program as A Form of Bureaucratic Reformation in Public Service Field (Study at Gorontalo Regency). A bureaucratic reformation in public service field called Government Mobile is a popular program at Gorontalo Regency. Government Mobile Program is a kind of direct service to the community, or in other words, it is a ball-pickup service. The origin of this program derives from the intention to change the old view or paradigm which still considers the government as the servant behind the desk. The government is expected to change into giving more emphasizes to provide direct service to the communities and to meet their demand in quick and precise ways. Implementation process was comprised of three processes, mainly planning, implementation and evaluation. The actor behind implementation includes government as service provider and communities as service receiver. Main goal and target is providing direct service to the communities. The supporting factors to this program involves leadership commitment, SKPD commitment, clear regulation to this program and community participation. Constraining factors also is limited timing, lacking of information and less reliable structures and infrastructures. Keywords: government mobile, bureaucratic reformation, public service Abstrak: Program Government Mobile Sebagai Bentuk Reformasi Birokrasi Di Bidang Pelayanan Publik (Studi di Kabupaten Gorontalo). Reformasi birokrasi di bidang pelayanan publik yang disebut Government Mobile menjadi program primadona di Kabupaten Gorontalo. Program Government Mobile berbentuk pelayanan langsung kepada masyarakat, dengan kata lain pelayanan jemput bola. Asal mula program ini yaitu ingin merubah pandangan atau paradigma lama yang menganggap pemerintah hanya melayani di belakang meja menjadi pemerintah yang mengutamakan pelayanan secara langsung kepada masyarakat dengan cepat dan tepat dan memenuhi kebutuhan mereka. Dalam aspek proses pelaksanaan program Government Mobile terdiri dari tiga proses yaitu perencanaan, pelaksanaan dan evaluasi. Aktor yang terlibat dalam pelaksanaan yaitu pemerintah sebagai pemberi pelayanan dan masyarakat yang menerima pelayanan. Sasaran dan tujuan utama program ini adalah pelayanan secara langsung kepada masyarakat yang membutuhkan. Faktor pendukung dari program ini yaitu untuk adalah komitmen pemimpin, komitmen dari SKPD dan peraturan yang jelas dan partisipasi masyarakat. Faktor penghambat yaitu rentan waktu yang terbatas, anggaran, informasi yang kurang dan fasilitas, sarana dan prasarana yang kurang memadai. Kata Kunci: Government Mobile, Reformasi Birokrasi, Pelayanan PublikÂ